Landscape Mapping: Investigating the Scope of Information Systems and Technology in Contemporary Organizations - Karlina Napu (West Science Information System and Technology, 2024)
In today's fast-paced business environment, the integration of Information Systems (IS) and technology is crucial for organizational success. This research aims to explore the landscape of Information Systems and Technology (IST) within contemporary organizations, investigating its multifaceted dimensions across diverse organizational contexts. Through a systematic examination, this study seeks to shed light on the intricate relationships between technology and organizational functionality, offering insights into IST deployment, utilization, and management strategies. By employing bibliometric analysis, thematic mapping, and author collaboration network analysis, this research provides a comprehensive understanding of IST research dynamics, trends, and future directions. The findings not only contribute to scholarly discourse but also offer practical implications for organizational stakeholders, policymakers, and technology practitioners.